A study on association between respiratory tract infection and serum 25 (OH) vitamin D level in children - Sah, Rajesh Kumar; Kumar, Hemant (International Journal of Contemporary Pediatrics, 2020)
Background: Acute respiratory tract infection are a major cause of global morbidity and mortality. Observational studies report consistent independent association between low serum concentration of 25-hydroxy-vitamin D and susceptibility to acute respiratory tract infection. This study was done to assess serum vitamin D level in children and correlation with respiratory tract infection. Methods: The present study was undertaken in department of paediatrics medicine, Patna Medical College and Hospital in patients attending out-patients department (OPD) as well as admitted in in-patients department (IPD). Assessment of serum 25(OH) Vitamin D was done by the enzyme immunoassay kit at Patna Medical College and Hospital. Results: The mean serum vitamin D level in cases was (20.52±5.64 ng/ml) where as in control group was (26.46±4.52 ng/ml) with a statically significant p value of <0.0001, hence cases are associated with vitamin D deficiency. Conclusions: The finding in this study showed significantly decreased mean serum vitamin D level in cases than that of control which implies that vitamin D deficiency predisposes to respiratory tract infection in children.